2019
DOI: 10.1111/nup.12282
|View full text |Cite
|
Sign up to set email alerts
|

Complicating nursing's views on religion and politics in healthcare

Abstract: Nursing, with its socially embedded theory and practice, inevitably operates in the realm of power and politics. One of these political sites is that of religion, which to varying degrees continues to shape beliefs about health and illness, the delivery of healthcare services and the nurse–patient encounter. In this paper, I attempt to complicate nursing's views on religion and politics in healthcare, with the intent of thinking critically and philosophically about questions that arise at the intersection of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 50 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Even those who are active, participating, observant Christians are not in agreement about the place of Christian symbols and practices in the public sphere. Christianity is richly textured in Canada and includes a wide range of approaches to the public presence of the Christian message, symbols, and practices (Bramadat and Seljak 2008;Reimer-Kirkham 2019;Young and Shipley 2020).…”
Section: Decline and Varieties Of Institutional Religionmentioning
confidence: 99%
“…Even those who are active, participating, observant Christians are not in agreement about the place of Christian symbols and practices in the public sphere. Christianity is richly textured in Canada and includes a wide range of approaches to the public presence of the Christian message, symbols, and practices (Bramadat and Seljak 2008;Reimer-Kirkham 2019;Young and Shipley 2020).…”
Section: Decline and Varieties Of Institutional Religionmentioning
confidence: 99%
“…Any interference, restriction or forced elimination of a patient's religious experience must therefore have a negative impact on the patient's personal condition. Religiousness is another means of discovering man's purposes (Cullen, 2016; Reimer‐Kirkham, 2019).…”
Section: Man As a Personmentioning
confidence: 99%
“…In this framework, the literature reveals that nurses have examined different spiritual perspectives. Stephenson and Hebeshy [ 11 ] pointed out that spiritual care should be incorporated into care plans and that nurses need updated knowledge and training on different forms of spirituality [ 12 , 13 , 14 ]. Other research found that the effectiveness of nursing care depended on nurses’ awareness of and sensitivity to the spiritual needs of their patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there is a concerted effort for spiritual assistance and spiritual support to be an integral part of the role of the nurse [ 19 , 20 ]. In clinical nursing practice, it is frequently unclear how to engage patients in spiritual care, especially in complex health systems and societies characterized by secularism and religious pluralism [ 12 , 14 , 21 ]. Although the role of spiritual care in palliative care and oncology is well recognized, less is known about its role in other areas of nursing, where spirituality and spiritual care are often neglected or absent [ 5 ].…”
Section: Introductionmentioning
confidence: 99%